Demand dynamics across secondary German Book markets: an information aggregation and synthetization approach - Helm, Christopher; Herberger, Tim Alexander; Tyrell, Marcel (Information Systems and E-Business Management, 2021)
This paper focuses on the increasing competition between resale opportunities for heterogeneous items with limited demand, i.e. long-tail products. This paper examines if commercial dealers offer higher purchase prices than purchase prices fixed in public auctions. To analyze this issue, we review options for customers to resell their belongings online after use. We use a proprietary software system to download, validate, and join item data across 14 data sources, like Amazon, eBay, and twelve commercial dealers in Germany for 1673 textbooks. We analyze the question which option to resell belongings online maximizes profit of the seller, while controlling for item, demand, supply, and auction specific characteristics. Besides a detailed analysis of the price spread, we exploit listing decisions among those resale options by non-commercial dealers and execute an arbitrage trading strategy using a purely deterministic model. We find that commercial dealers offer a higher purchase price than public auctions. We argue that commercial dealers offer these higher prices as they can shift item demand over time. In addition, prices in public auctions could be depressed because on consumer-to-consumer online auction markets a strategy called “sniping” is widespread, which might hamper the price mechanism. Our results are relevant for end-consumers who are willing to dispose of items in their belonging and for commercial dealers who want to optimize their sourcing. These results can be devolved on market microstructures of other standardized products like, for example, financial products.
CRIS-Team Scopus Importer:2021-04-19
Keywords: Commercial dealers; Consumer economics; Market design; Non-commercial dealers; Online auctions; Resale market; Sniping